Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 1999)
We have today a large network of Engineering colleges and polytechnic in the country, specially in the four southern states namely Maharashtra, Andhra Pradesh, Karnataka and Tamilnadu. A phenomenal growth has occurred that could not even be dreamt, some years back.